PENILAIAN DAN SELEKSI GALUR KACANG HIJAU (Phaseolusradiata) HASIL KOLKISIN M1 DAN M2 - Herman Herman; Fitmawati Fitmawati; Dewi Indriyani Roslim; Fathurrahman Fathurrahman; Okyarni Nuzila (UIR Press, 2012)
Plant selection of mutant with cholcisin of 507 accessions planted at the experimental farm of FMIPA Biology Riau University. A Completely Randomized Design was used in this research. Observation result for 15 accessions M1 and M2 of mutant mung bean pea had a potential to be developed as a high yielding plant. Based on observation of plant height characteristics for mutant mung bean was obtained the plant height ranging from 89 to 100.5 cm, flowering age ranging from 32 to 34 days (50%), pod age ranging from 37 to 53 days, harvested pod number ranging from 68 to 70 (50% mature), and pod weight ranging from 39-53 g/heaviest plant. For mung bean, cholcisin mutation induction could induct to emerge mutant generation. This mutant had better productivity comparing to local green pea found in Sendayan Kampar Riau before being inducted. Mutant which showed the best result was M1 and M4 colleting big fruit, 80% of mature and little trikom generation.